2014
DOI: 10.1016/j.pmrj.2014.08.783
|View full text |Cite
|
Sign up to set email alerts
|

Poster 408 Use of Virtual Patient Simulation in Pressure Ulcer and Patient Safety Education in Physical Medicine and Rehabilitation: An Evidence and Problem‐Based Learning Experience for Medical Students

Abstract: reflexes throughout. Past medical history was significant for an episode of diplopia and visual loss in her 30s, which was diagnosed as optic neuritis and treated with steroids. An MRI at that time was inconclusive. Considering multiple sclerosis versus lumbar stenosis, an MRI of her low back and brain was ordered. Setting: Tertiary care outpatient clinic. Results or Clinical Course: Lumbar spine imaging revealed mild lumbar spondylosis at L5-S1 and no evidence of stenosis. Neuroimaging revealed classic distri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This study is consistent with prior research that demonstrates utility of simulation training in PM&R education. Simulation techniques have been applied broadly within PM&R education, with studies showing successful use in the instruction of musculoskeletal ultrasound, needle driving for interventional procedures, pressure ulcer and patient safety education, botulinum toxin injections and peripheral motor blocks, among others . Pilot studies have reported the feasibility of using simulation‐based education for teaching autonomic dysreflexia, a common urgent medical complication that occurs in patients with complete spinal cord injuries at T6 or above, to PGY‐2 PM&R residents .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study is consistent with prior research that demonstrates utility of simulation training in PM&R education. Simulation techniques have been applied broadly within PM&R education, with studies showing successful use in the instruction of musculoskeletal ultrasound, needle driving for interventional procedures, pressure ulcer and patient safety education, botulinum toxin injections and peripheral motor blocks, among others . Pilot studies have reported the feasibility of using simulation‐based education for teaching autonomic dysreflexia, a common urgent medical complication that occurs in patients with complete spinal cord injuries at T6 or above, to PGY‐2 PM&R residents .…”
Section: Discussionmentioning
confidence: 99%
“…Simulation training aims to mimic real‐life experience and is consistently associated with positive effects on knowledge, skills, and patient‐related outcomes . There is good evidence to support the use of simulation‐based methods in PM&R education . However, little evidence exists on the use of simulation technology for the instruction of urgent medical complications to PM&R residents .…”
Section: Introductionmentioning
confidence: 99%